Kewenangan Pengelolaan Lingkungan Hidup Oleh Pemerintahan Daerah Dalam Perspektif Otonomi Daerah - Nikita Dea Angelina; Putri Agustin; Yahdi Oktama (CV. Multi Kreasi Media, 2022)
Environment is unity space with all things, power, conditions, and living things, including humans and their behavior, which affects nature itself. Management of the environment life is a responsibility and mutual obligations between society and government, however in further implementation the setting is determined by government. To further examine this, the author uses normative research methods, namely using documents and various secondary data such as legislation, legal theory, and can be in the form of expert opinions regarding the division of authority in the environmental field including: Central Government, Government Province and Regency Government or City as contained in the Attachment of the Act Number 23 of 2014 concerning Regional Government.